High-resolution measurement and analysis of the transient secondary flow field in a turbine cascade. (November 2014) - Wang, Shun-sen; Sun, Hao; Di, Juan; Mao, Jing-ru; Li, Jun; Cai, Liu-xi
Combining an improved particle image velocimetry technique with a far-field microscope, a high-resolution quantitative measurement of the transient secondary flow field in an annular turbine cascade is conducted through moving the laser light sheet to follow the primary flow. The measuring results revealed the transient behavior and strong unsteadiness of the secondary flow in a cascade for the first time. It is confirmed that the suction side leg of the horseshoe vortex rotates around the passage vortex along the rotating direction of passage vortex. In the secondary flow of cascade, the formation, development and decay of Hopf bifurcations caused by the competition between the tensile deformation and the dissipation, have become a major behavior of vortex evolution. Driven by the interaction between the passage vortex and the suction side leg of the horseshoe vortex as well as the transverse pressure gradient, the passage vortex was pushed to the suction surface and ultimately formed the wall vortex. Furthermore, the strength of secondary vortex was enhanced with the increase of aerodynamic parameters, though the scale of vortex was gradually shrinking and the limit cycle concentrated at the core of vortex. However, no change happened to the location of vortex core and the structure of vortex. The computational fluid dynamics results revealed that the results using the SST k - ω model was the closest to the experiment results in the topological structure, the evolution process of secondary flow and the magnitude estimation, followed by those with the RNG k - ɛ model. The results with standard k - ɛ model were clearly inconsistent with the experimental results.